Diversity and evolution of membrane intrinsic proteins - Abascal, Federico; Irisarri, Iker; Zardoya, Rafael (Biochimica et biophysica acta, 2014)
Membrane intrinsic proteins (MIPs) are the proteins in charge of regulating water transport into cells. Because of this essential function, the MIP family is ancient, widespread, and highly diverse. The rapidly accumulating genomic and transcriptomic data from previously poorly known groups such as unicellular eukaryotes, fungi, green algae, mosses, and non-vertebrate animals are contributing to expand our view of MIP evolution throughout the diversity of life. Here, by analyzing more than 1700 sequences, we provide an updated and comprehensive phylogeny of MIPs The reconstructed phylogeny supports (i) deep orthology of X intrinsic proteins (XIPs; present from unicellular eukaryotes to plants); (ii) that the origin of small intrinsic proteins (SIPs) traces back to the common ancestor of all plants; and (iii) the expansion of aquaglyceroporins (GLPs) in Oomycetes, as well as their loss in vascular plants and in the ancestor of endopterygote insects. Additionally, conserved positions in the protein, and residues involved in glycerol selectivity are reviewed within a phylogenetic framework. Furthermore, functional diversification of human and Arabidopsis paralogs are analyzed in an evolutionary genomic context. Our results show that while bacteria and archaea generally function with one copy of each a water channel (aquaporin or AQP) and a GLP, recurrent independent expansions have greatly diversified the structures and functions of the different members of both MIP paralog subfamilies throughout eukaryote evolution (and not only in flowering plants and vertebrates, as previously thought). This article is part of a Special Issue entitled Aquaporins. [Display omitted] •An updated phylogeny of MIPs is reconstructed.•Recurrent expansions of AQPs and GLPs occurred throughout eukaryote evolution.•Functional diversification of these proteins conferred adaptive advantages.•XIPs are found to be present from unicellular eukaryotes to plants.•The origin of SIPs traces back to the common ancestor of all plants.